364 Zero Itch in Eyes Treated With Olopatadine Hydrochloride Ophthalmic Solution, 0.2% in Bilateral Conjunctival Allergen Challenge Studies - Blaiss, Michael S. (World Allergy Organization Journal, 2012)
PURPOSE: To further assess the prevention of ocular itching with olopatadine hydrochloride ophthalmic solution, 0.2% (OLO) in patients with allergic conjunctivitis. METHODS: This was a post-hoc analysis of 85 patients participating in 2 prospective, randomized, double-masked bilateral conjunctival allergen challenge (CAC) studies. Patients received OLO in one eye and placebo (vehicle) in the contralateral eye. Ocular itching was self-assessed by patients and rated on a scale of 0 (none) to 4 (severe). To assess onset of action, eligible patients were challenged with antigen 27 minutes after dosing. To assess duration of action, patients were challenged with allergen 16 hours after dosing. The percentage of eyes with zero itching in both studies was assessed at 3 minutes post allergen challenge. RESULTS: The percentage of eyes with zero itch at the 3 minutes timepoint after the onset of action allergen challenge was 60.0% for OLO-treated eyes compared with 5.9% for vehicle-treated eyes (P < .0001, OLO vs vehicle). The percentage of eyes with zero itch at 3 minutes post allergen challenge following the 16-hour dosing was 59.8% for OLO-treated eyes compared with 22.0% for vehicle-treated eyes (P < .0001, OLO vs vehicle). CONCLUSIONS: In bilateral CAC studies, ocular itching was prevented in a higher percentage (P < .0001) of eyes treated with 0.2% olopatadine hydrochloride ophthalmic solution when compared with vehicle as early as 30 minutes and for at least 16 hours post dosing.